In vitro evaluation of the effectiveness of pediatric drugs and tooth brushing on the surface roughness of different restorative dental materials used in pedodontics - Yildiz, Şemsettin; Ataş, Osman (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Liquid oral drugs are frequently used in children. Knowing the effects of these drugs and individual oral hygiene brushing on the surface roughness (SR) of dental restorative materials with different contents used in pediatric dentistry is clinically important. Purpose: The aim is to assess the effects of various drugs and toothbrushes used in children on the SR of dental restorative materials. Methods: A total of 60 samples of different dental filling materials (polyacid-modified composite resin [compomer], glass ionomer cement [GIC], and composite resin) were prepared. The specimens were divided into six solution groups (distilled water, antibiotics, analgesics, antiepileptics, bronchodilators, and anti-allergic drugs). For each group (n = 5), two subgroups (brushing and non-brushing) were created. Surface roughness values (Ra) were measured at baseline and at the first and fourth weeks using a profilometer. The data were analyzed using analysis of variance, post-hoc analysis, and the Bonferroni test (p < 0.05). Results: The highest roughness value among all drug groups was detected in the non-resin-containing traditional GIC material. In addition, the brushing condition had a statistically significant effect on SR values (p < 0.05). The smallest change in roughness from baseline to the fourth week was observed in the non-brushed composite material in the Amoklavin group, whereas the largest change was observed in the brushed GIC material in the Depakin solution. Conclusion: Drug solutions and brushing affect the SR of restorative materials, with resin-containing materials being less affected than GIC.